Banking reforms and globalisation - Shrivastava, M. P. (Mohan Prasad), 1953-; Pandey, Pradeep Kumar, 1958-; Vidyarthi, V. P. (New Delhi : APH Pub. Corp., 2007)
Contributed articles with reference to India.
Includes bibliographical references and index.
Keywords: Banks and banking -- Government policy -- India; Bank management -- India; India -- Economic policy -- 1991-